Examining Differential Item Functioning of the Rosenberg Self-Esteem Scale across Eight Countries (in Press) - Baranik, Lisa E. (Institutional Knowledge at Singapore Management University, 2008)
We examined the differential item functioning (DIF) of Rosenberg's (1965) Self-Esteem Scale (RSES) and compared scores from U.S. participants with those from 7 other countries: Canada, Germany, New Zealand, Kenya, South Africa, Singapore, and Taiwan. Results indicate that DIF was present in all comparisons. Moreover, controlling for latent self-esteem, participants from individualistic countries had an easier time reporting high self-esteem on self-competence-related items, whereas participants from communal countries had an easier time reporting high self-esteem on self-liking items (Tafarodi & Milne, 2002). After adjusting for DIF, we found larger mean self-esteem differences between the countries than observed scores initially indicated. The suitability of the RSES, and the importance of examining DIF, for cross-cultural research are discussed.